In Nuwe belydenisskrif vir die Nederduitsch Hervormde Kerk van Afrika? - Wyk, I. W. C. van (Hervormde teologiese studies, 1999)
A new confession for the Nederduitsch Hervormde Kerk van Afrika? In this article the question is asked whether a new creed or confession is possible and in this point in time necessary. The answer is that there should always be room for new creeds and confessions. Although there might be many reasons for a new confession, the present time does not really seem to call for such a confession. But we must remain open for a new confession at any time. In the meantime we must actualise the old creeds and confessions, and we must consider subscibing to other Reformed confessions as well as confessions from this age that could be relevant and important to us.